Factors Associated with Health Care Professionals’ Attitude Toward the Presumed Consent System - Tumin, Makmor; Tafran, Khaled; Satar, Nurulhuda Mohd; Ng, Kok Peng; Manikam, Rishya; Tang, Li Yoong; Chong, Mei Chan (Baskent University, 2019)
Objectives: This paper explores health care pro - fessionals’ potential attitude toward organ donation if the presumed consent system were to be im - plemented in Malaysia, as well as factors associated with this attitude. Materials and Methods: We used self-administered questionnaires to investigate the attitude of 382 health care professionals from the University of Malaya Medical Center between January and February 2014. The responses were analyzed using logistic regression. Results: Of the 382 respondents, 175 (45.8%) stated that they would officially object to organ donation if the presumed consent system were to be imple - mented, whereas the remaining 207 (54.2%) stated that they would not object. The logistic regression showed that health care professionals from the Malay ethnic group were more likely to object than those from Chinese (adjusted odds ratio of 0.342; P =.001) and Indian and other (adjusted odds ratio of 0.341; P =.003) ethnic groups. Health care professionals earning 3000 Malaysian Ringgit or below were more likely to object than those earning above 3000 Malaysian Ringgit (adjusted odds ratio of 1.919; P =.006). Moreover, respondents who were initially unwilling to donate organs, regardless of the donation system, were more likely to object under the presumed consent system than those who were initially willing to donate (adjusted odds ratio of 2.765; P <.001). Conclusions: Health care professionals in Malaysia have a relatively negative attitude toward the presumed consent system, which does not encourage the implementation of this system in the country at present. To pave the way for a successful implementation of the presumed consent system, efforts should be initiated to enhance the attitude of health care professionals toward this system. In particular, these efforts should at most target the health care professionals who are Malay, earn a low income, and have a negative default attitude toward deceased donation. © Başkent University 2019.